Repositioning Islamic social reporting as a strategic moderator: Evidence from Indonesian Islamic banks - Achmad Soediro; Eogenie Lakilaki; Media Kusumawardani; Muhammad Farhan (Faculty of Islamic Economics and Business, UIN Salatiga, 2024)
This study aims to assess the effect of Islamic Social Reporting (ISR) on the relationship between financial performance and firm value in Indonesian Islamic banks. This study utilizes the Moderated Regression Analysis model, with ISR serving as the moderating variable, financial performance metrics (Financing to Deposit Ratio [FDR], Return on Assets [ROA], and Capital Adequacy Ratio [CAR]) as the independent variables, and firm value (EVA) as the dependent variable. The study focuses on ten Islamic commercial banks in Indonesia from 2017 to 2023 and is based on the analysis of 70 annual financial reports, utilizing Moderated Regression Analysis. The findings indicate that ISR significantly moderates and strengthens the relationship between ROA and EVA. This underscores the critical role of ISR reporting in helping regulators develop a more comprehensive framework and in reinforcing the industry’s adherence to Islamic economic principles. By exploring the nuanced role of ISR in amplifying financial signals like ROA, this study subtly repositions ISR from a mere reporting obligation to a strategic element that deepens the value relevance of Islamic financial disclosures.